Development and integration of new ultra low k materials & processes for high reliability microelectronics - Mhaisalkar, Subodh Gautam. (2008)
The project will focus on the integration of the ultra low k materials into advanced silicon processes so as to yield highly reliable devices to meet the requirements of next generation integrated circuits. Reliability initiatives will include phenomenon such as stress and electro migration, time dependent dielectric breakdown (TDDB), development of new methodologies to characterize the material properties such as adhesion strength, moisture absorption and hygrostress, and to study the impact of polymer materials as well as porosity on thermal conductivity, thermo mechanical stresses on the device as well as packaging levels. New designs and structures of ultra low k materials alternated with silicon dioxide and silicon nitride materials will be investigated in order to improve the reliability of the packaged flip chip interconnects. Finally, methodologies to study device and package level reliabilities with numerical modeling techniques will also be developed.